Gender violence through the eyes of the Bajan youth: using Photovoice methods in small island states. Issue 4 (20th October 2021) - Ascroft, Elizabeth
Abstract : The 'culture of silence' around gender violence is an acute challenge in Barbados. As in other small island spaces, a fear of gossip and barriers around anonymity limit the space available for young people to discuss and disclose cases. Despite young people having been identified as a target group for gender violence prevention work, there is a notable gap in Caribbean scholarship around qualitative research with young people. To contribute to this oversight, this article is a part-reflection from a research project that sought to amplify young Barbadian's perceptions of gender violence. The focus of this article is methodological, providing fresh insight into the 'what, why and how' of using Photovoice methods in small island contexts. It offers an understanding of what the approach looks like, its value in exploring gender violence phenomena and reflects on its potential to stimulate critical consciousness as participatory-action research. It concludes by advocating Photovoice methods in spaces where young voices are marginalised.